2015
DOI: 10.1007/s10661-015-4991-7
|View full text |Cite
|
Sign up to set email alerts
|

The physicochemical characteristics and anaerobic degradability of desiccated coconut industry waste water

Abstract: Desiccated coconut industries (DCI) create various intermediates from fresh coconut kernel for cosmetic, pharmaceutical and food industries. The mechanized and non-mechanized DCI process between 10,000 and 100,000 nuts/day to discharge 6-150 m(3) of malodorous waste water leading to a discharge of 264-6642 kg chemical oxygen demand (COD) daily. In these units, three main types of waste water streams are coconut kernel water, kernel wash water and virgin oil waste water. The effluent streams contain lipids (1-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…MLM is widely used for biogas . MGM showed a good fit to the cumulative methane production data from organic wastes derived from desiccated coconut industries with a sigmoid pattern . In order to achieve a better fit in this study, four models were compared and MHM was successfully introduced as an alternative model.…”
Section: Resultsmentioning
confidence: 99%
“…MLM is widely used for biogas . MGM showed a good fit to the cumulative methane production data from organic wastes derived from desiccated coconut industries with a sigmoid pattern . In order to achieve a better fit in this study, four models were compared and MHM was successfully introduced as an alternative model.…”
Section: Resultsmentioning
confidence: 99%
“…This is the case when the substrate is difficult to degrade [49]. The modified Gompertz model has been widely used in the simulation of biogas and methane production results [54][55][56][57]. This model can predict the lag-phase of the process, a period associated with the hydrolysis of the substrate in the digester.…”
Section: Biogas Productionmentioning
confidence: 99%
“…A Seoul, Korea lab-scale study on thermophilic anaerobic digestion of food waste showed that methanogenic activity was impacted at high OLR, which led to accumulation of volatile fatty acids (VFAs) and concomitant decrease in pH . Chanakya et al (2015) reported that coconut processing wastewater from three different industrial processing separate streams: coconut kernel water, kernel wash water, and virgin oil wastewater was treated anaerobically.…”
Section: Biological Treatment Including Anaerobic Treatmentmentioning
confidence: 99%